The heuristic method: a change in the level of achievement of the evaluation of the competences of the area of mathematics - Jamanca Sánchez, Dina E. (2022)
The objective of this research is to demonstrate that the heuristic method increases the level of learning of a group of students from I.E.3003-R´ımac in the competences of the area of mathematics. In its implementation, teachers play the role of mediator and strategist following the didactic processes: understanding of the problem, design and execution of the strategy, reflection, formalization of the concepts and transfer. The proper application of the heuristic method promotes the development of intuitive, logical, critical and creative thinking in students. The applied methodology consisted of working with two groups: 6th B students, who were called the experimental group and the heuristic method was applied, and 6th A students, called the control group (x), with whom the traditional method. The procedure consisted of administering an entry test to both groups before the intervention and an exit test after the intervention.